2020
DOI: 10.29252/rbmb.9.3.278
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Quercetin and Melatonin on Indomethacin Induced Gastric Ulcers in Rats

Abstract: Background: Medications to prevent the development of NSAID-induced gastric ulcers have a large range of unpleasant side effects. Recent efforts have been focused on determining safer alternative nontoxic and natural forms of anti-ulcer treatments. Methods: Twenty-four male rats were divided into 4 groups: 1: control group that received no treatment; 2: the indomethacin-treated group that received 20 mg/kg of indomethacin for 2 days to induce the development of gastric ulcers; 3: quercetin-treated group that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Likewise, a similar fragmentation pattern was observed for kaempferol and its glycosides, e.g., peaks 8, 13 and 16, corresponded to kaempferol- O -rhamnosyl-di-hexoside ( Figure S2 ), kaempferol- O -hexosyl-rhamnoside and kaempferol- O -hexoside ( Figure S3 ), respectively, also showing the typical neutral losses of their sugar residues with characteristic product ions at m / z 287, typical for the kaempferol aglycon fragment ( Table 3 ). Both quercetin and kaempferol are flavonols known for their anti-inflammatory and antioxidant effects in in vitro studies [ 33 ] Moreover, several reports showed the potential of quercetin ameliorating activity against indomethacin-induced gastric ulcers in rats, owing to its anti-apoptotic effect [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, a similar fragmentation pattern was observed for kaempferol and its glycosides, e.g., peaks 8, 13 and 16, corresponded to kaempferol- O -rhamnosyl-di-hexoside ( Figure S2 ), kaempferol- O -hexosyl-rhamnoside and kaempferol- O -hexoside ( Figure S3 ), respectively, also showing the typical neutral losses of their sugar residues with characteristic product ions at m / z 287, typical for the kaempferol aglycon fragment ( Table 3 ). Both quercetin and kaempferol are flavonols known for their anti-inflammatory and antioxidant effects in in vitro studies [ 33 ] Moreover, several reports showed the potential of quercetin ameliorating activity against indomethacin-induced gastric ulcers in rats, owing to its anti-apoptotic effect [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism for increasing Bcl-2 level was that quercetin has an antiapoptotic impact against aspirin-induced apoptosis in gastric tissue that was mediated through inhibiting the c-Jun N-terminal kinases (JNK) and ERK-mediated apoptotic pathways (Abdel-Tawab et al, 2020). The mechanism for decreasing NF-kB level was that the NF-kB pathway, which is involved in the generation of proinflammatory cytokines including tumour necrosis factor-(TNF-), interleukin-6 (IL-6), and interleukin-1 (IL-1), is suppressed by quercetin, which suppresses inflammation via neutrophil infiltration (Cheng et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Due to its pharmacological and biological activities, quercetin has a significant role in the prevention of cardiovascular diseases, obesity, type 2 diabetes, asthma, cancer, viral infections, mood disorders, and many others [2][3][4][5][6][7][8][9][10]. Its anti-inflammatory and antiulcer effects have been demonstrated [11][12][13][14]. It stimulates neurogenesis and has been shown to improve memory [12,15,16].…”
Section: Introductionmentioning
confidence: 99%